Understanding how education/support groups help lone mothers - Cameron Ruth; Jack Susan; Kenny Meghan; Lipman Ellen L; Secord Margaret; Byrne Carolyn (BMC, 2010)
Abstract Background Lone-mother led families are at increased risk of psychosocial disadvantage, social isolation and mental health morbidity. Community-based programs are more accessible for families seeking assistance. We examine the experiences of eight lone mothers participating in a larger randomized controlled trial (RCT) of a community-based education/support group program using mixed methods. Methods A purposeful sample of eight mothers participating in the intervention arm of an RCT of community-based support/education groups was selected for the qualitative study. Individual interviews asked mothers about themselves and their relationships with their children before and after the group. Interviews were taped, transcribed and content analysis was used to code and interpret the data. Quantitative data collected in the RCT were used to describe these mothers. Results Mothers participating in the RCT and qualitative study experienced multiple difficulties, including financial and mood problems. These mothers reported that before participating in the group, they had shared experiences of social isolation, stigma, a sense of failure, poor relationships with their children and difficulties with financial management. After the group, mothers identified improved self-esteem, support from other mothers, improved parenting skills and improved communication with their children as outcomes of group participation. Conclusions The qualitative data revealed mothers' perceptions of specific areas that improved by participating in the group. The utility of complementary information provided by qualitative and quantitative methods in understanding program impact, as well as the need for broader assistance is noted.